A Linguistic Study on Advertising and Marketing Communication: Exploring the Influence of Language in Advertising and Marketing Communication (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Advertising or advertizing in business isa form of marketing communication usedto encourage, persuade, or manipulate an audience (viewers,readers or listeners; sometimes a specific group) to take or continue to takesome action. Most commonly, the desired result is to drive consumer behaviorwith respect to a commercial offering, although political and ideologicaladvertising is also common. This type of work belongs to a categorycalled affective labor.